Anemia in Pregnancy: Cause and Effect - Ananda Karunia Ramadhan; Ario Danianto; Rifana Cholidah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
One of the most common complications associated with pregnancy is anemia. Severe anemia that occurs during pregnancy has adverse effects on both the mother and the fetus. This literature review aims to provide related information related to how anemia can occur in pregnancy, what are the risk factors and causes of anemia in pregnancy, and the impact of anemia on pregnant women and their fetuses. We searched from online databases and used review articles, research, guidelines from professional organizations, such as World Health Organization and Ministry of Health Republic of Indonesia. Result: In general, pregnant women will experience a decrease in hemoglobin concentration due to the physiological role of hemodelution during pregnancy. However, this condition will be worsened and make pregnant women fall into anemia when accompanied by other factors such as iron deficiency, folic acid deficiency, infection, non ideal BMI (Body Mass Index), and congenital blood diseases. As a result, severe anemia that occurs during pregnancy has adverse effects on both the mother and the fetus. Conclusion: It is important to understand the factors that cause anemia in pregnancy to avoid adverse effects on pregnant women and their fetuses or children.